Analisa Penggunaan Sistem Accurate dalam Pencatatan Transaksi Pembelian Semen pada PT XYZ - Dea Devira Veronika; Muslimin Muslimin (Pusat Riset dan Inovasi Nasional, 2026)
This research was conducted to examine the implementation of the Accurate system in recording cement purchase transactions at PT. XYZ and to evaluate its effectiveness in supporting the company's operational activities. A qualitative approach was employed, emphasizing the analysis of descriptive data in the form of words and documents. The study was carried out using a case study method to obtain an in-depth understanding of the phenomenon being investigated. During the internship period, data were collected through interviews, observations, and documentation techniques. Research shows that the Accurate system helps companies record purchases in a more organised, faster and more accurate way than the manual method using Microsoft Excel. The Accurate system can automatically record purchase invoices, business debts, suppliers and the inventory of goods. This makes the accounting department more efficient. Accurate helps to reduce the risk of recording errors and makes it easier to find transaction data. However, when it is being used, there are still several problems, such as delays in entering transaction data, mistakes when entering names or account numbers, and being unable to change invoices after a certain amount of time. To get around these problems, the company checks the transaction data again and makes sure that the recording process is more consistent. Research results show that the Accurate system is effective in PT. XYZ can help make sure that the process of recording cement purchases is effective and efficient. It can also help make sure that financial information is more accurate and joined up.